THE (IM) POSSIBILITY OF DISCUSSING LAW IN THESIS IN POPULAR ACTION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The Popular Action, a genuineinstrument for thedefenseof transindividual interests, represents a legal weapon for thecitizen'scontrolofactsharmfultoestablishedconstitutionalinterests. Therefore, wesoughttoevaluate in thisarticlewhethernormativeactscanbeobjectof Popular Action, as well as toevaluatetheconstitutionalitycontrol in these cases, whether it isallowedornot. It wasobservedthatthecurrentjurisprudenceconsidersadequatewaytochallengenormativeactsthat are, in fact, trueadministrativeacts, devoidofthecharacterof Law, thatis, theelementsofabstractionandgenerality. Moreover, it hasbeenfoundthatan incidental declarationofunconstitutionalityispossible, providedthatthisisnottherequestofthe Popular Action, but a consequencethereof. Finally, it wasevidencedthatthereis in thejurisprudencejudgedthatextinguishthe Popular Actionif it isshownthattherewasnotevenspecificitybythePlaintiffof a case contractofdamagetopublicpropertyandmorality, beingclearlyused for annulmentof Law, in usurpationofjurisdictionoftheSupremeCourt.